A COMPREHENSIVE REVIEW OF MODERN CYBERSECURITY THREATS, VULNERABILITIES, AND MITIGATION STRATEGIES (Contemporary Journal of Social Science Review, 2025)
The rapid proliferation of digital technologies, cloud computing, the Internet of Things (IoT), and artificial intelligence has transformed modern society while simultaneously introducing unprecedented cybersecurity challenges. This comprehensive review examines the evolving landscape of cyber threats, vulnerabilities across multiple domains, and contemporary mitigation strategies. The paper synthesizes findings from an extensive analysis of peer-reviewed literature, industry reports, and documented cyber incidents from 2000 to 2024. A systematic literature review methodology was employed, following PRISMA guidelines, to select 120 relevant studies from major databases including IEEE Xplore, ScienceDirect, ACM Digital Library, and Google Scholar. Key findings reveal that ransomware attacks surged by 72% in 2022, with global damages projected to reach $265 billion by 2031. Advanced Persistent Threats (APTs), supply chain attacks, and AI-powered malware represent emerging threat vectors that challenge traditional defense mechanisms. The study identifies weak authentication mechanisms, firmware vulnerabilities, insecure communication protocols, and supply chain risks as persistent challenges across IoT, FinTech, and critical infrastructure sectors. Mitigation strategies including zero-trust architecture, behavioral analytics, AI-driven intrusion detection systems, and blockchain-based authentication demonstrate promising results. However, resource-constrained IoT devices and legacy industrial control systems remain particularly vulnerable due to limited computational capacity for robust encryption. The paper concludes by identifying research gaps and proposing future directions for cybersecurity resilience in an increasingly interconnected digital ecosystem.